Professional burnout in teachers: nature, signs, prevention (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article deals with the problem of professional burnout inteachers. The essence of the concept of «occupational burnout syndrome»(SPV) is investigated. The main signs and symptoms of occupationalburnout syndrome are presented. The reasons for the current tendencyto increase the number of teachers with SPV are substantiated. Thescientific literature on the nature, psychological and pedagogical reasons,manifestations and prevention of SPV in teachers is reviewed. The resultsof previous studies by the method of «Diagnosis of professional burnout»by K. Maslach and S. Jackson are analyzed. The main criteria for the SPVare determined. And also prophylactic methods of SPV based on scientificliterature are proposed.
Keywords: «professional burnout syndrome»; «emotional burnout»; symptoms of PDS; emotional exhaustion; depersonalization; reductions in one’s own personal achievements; prevention